Ursachen und Auswirkungen der Entvölkerung von Éire zwischen 1841 und 1951 - Leister, Ingeborg (ERDKUNDE, 1956)
It is a phenomenon unique in Europe that the population of a country has been reduced by emigration to half its former size, as has happened in Ireland. The first section of the paper traces the population development and living conditions within the boundaries of the present Irish Republic up to the pronounced break which was caused by the Great Famine. The mass emigration of Irish people which took place during the first, decades after the Great Famine declined somewhat later on, but even today emigration has not completely ceased. The depopulation, which affected almost exclusively the rural areas, varied considerably in the different countries. The decline of the agricultural population caused and facilitated far-reaching changes in the agricultural structure. Following this discussion of the consequences of the Great Famine is a brief characterisation of the present agricultural structure of the Irish Republic. An outline of the main reasons for the continuance of emigration leads over to an exposition of the governmental measures aimed at stemming emigration. Amongst them industrialisation is recognised as the most important since it is responsible for the fact that, during the quinquennium 1946-1951 the population increased for the first time since 1845. Also for the first time the population growth of greater Dublin surpassed the population loss of the rest of the country.